2020
DOI: 10.1002/pssr.201900682
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Plasmonic Nanodisk Positions Inside a Magnetic Medium on the Faraday Effect Enhancement

Abstract: Light localization by metal particles of nanometer size allows to not only control the propagation of light, but also enhance magneto‐optical effects. The influence of the immersion of gold nanodisks inside a transparent magnetic medium, namely, Bi‐substituted iron garnet, is investigated, and the optimal position of the nanoparticles within the magnetic material for a strong enhancement of the effect is unraveled. Three samples with periodic arrays of Au cylinders are studied: disks on the surface of the magn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Laser driven magnetization precession introduced by Kimel et al has been developed further and resulted in several breakthrough experimental demonstrations, i.e., the photomagnetic switching and optomagnetic all-optical spin wave emission in transparent dielectric ferrimagnets. In order to surpass the future applications in terms of low power consumption and low magnetic damping, yttrium iron garnet (YIG) is frequently used as a platform for magnonic devices. , The spin–orbit coupling and therefore interaction between light and spins is significantly enhanced when iron garnets with bismuth substitution (BIG) are used. …”
mentioning
confidence: 99%
“…Laser driven magnetization precession introduced by Kimel et al has been developed further and resulted in several breakthrough experimental demonstrations, i.e., the photomagnetic switching and optomagnetic all-optical spin wave emission in transparent dielectric ferrimagnets. In order to surpass the future applications in terms of low power consumption and low magnetic damping, yttrium iron garnet (YIG) is frequently used as a platform for magnonic devices. , The spin–orbit coupling and therefore interaction between light and spins is significantly enhanced when iron garnets with bismuth substitution (BIG) are used. …”
mentioning
confidence: 99%
“…Optical characteristics can be managed by the nanostructuring [1][2][3] or by controlling of the dielectric properties via illumination by powerful optical beam, short optical pulses, heating, application of the external magnetic field, etc. The latter case is relevant when a nanostructure contains magnetic components [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], and is the most interesting in context of the present work.…”
Section: Introductionmentioning
confidence: 99%
“…The linearly polarized input light reveals the polarization rotation after the transmittance through the magnetic material. The Faraday effect has been thoroughly studied in separate magnetic layers [20] as well as in the magnetoplasmonic nanostructures [17][18][19][21][22][23]. It was shown that in the magnetoplasmonic nanostructures the Faraday effect experiences the resonant peculiarities in the spectral range of the surface plasmon polariton (SPP) and waveguide (WG) optical modes excitation [21].…”
Section: Introductionmentioning
confidence: 99%
“…Another possibility to increase the resonance Q-factor is to introduce a magnetic material in the sensing structure and to utilize the magneto-optical measurements of the transverse magneto-optical Kerr effect (TMOKE) instead of optical reflectance spectra [ 5 , 19 , 20 , 21 , 22 ]. The magneto-optical response can be enhanced with a variety of metamaterials [ 23 , 24 , 25 , 26 ], plasmonic coatings, dielectric nanostructures [ 27 , 28 , 29 ], and photonic crystals [ 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%